Mathematics and music game in the function of child's social and emotional development - Rajić, Stajka (Array, 2020)
The paper presents empirical research, aiming to present the extent to which the application of the concrete mathematical and musical play contributes to the child’s social and emotional development. The research was conducted in two international schools in Belgrade, using the play titled ‘Musical Monkeys’ and in collaboration with the Music-Math team from Mexico who are the creators of the mentioned game. The results have shown that this kind of approach in working with children encourages activity and engagement, self-confidence, empathy, team work, integrity, tolerance and enthusiasm, while requiring and encouraging collaboration and constructive communication, cooperation and respect among students in the process of solving a set of mathematical and/ or musical tasks. The obtained results confirm that the children established connection between the mathematical and musical segments involving a high level of emotional and social skills – collaboration, communication, empathy, enthusiasm, commitment, curiosity for the game and felt benefits of team work, tolerance and respect while solving the given educational tasks.